1994
DOI: 10.1111/j.1553-2712.1994.tb02649.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Emergency‐procedure Teaching Laboratory for the Development of Proficiency in Tube Thoracostomy

Abstract: Objective: Emergency-procedure laboratories are not a standardized part of the curriculum for emergency medicine residency programs. The authors evaluated the efficacy of an emergency-procedure laboratory to teach medical students and residents the performance of tube thoracostomy.Methods: A prospective repeated-measures study of tube thoracostomy placement training was performed in an animal-laboratory setting. Participants were six first-postgraduate-year emergency medicine residents and six fourth-year medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…Traditionally, the training of chest tube placement has been accomplished using either animal or cadaver models 47,48 . Using a canine lab to train EM residents and fourth‐year medical students, Homan et al 49 found that repetition increased procedural speed and improved retention of skills. Chapman et al 50 demonstrated that paper and computer modeling of open thoracotomy did not increase procedural accuracy.…”
Section: Current Literature On Simulation‐based Procedural Traininmentioning
confidence: 99%
“…Traditionally, the training of chest tube placement has been accomplished using either animal or cadaver models 47,48 . Using a canine lab to train EM residents and fourth‐year medical students, Homan et al 49 found that repetition increased procedural speed and improved retention of skills. Chapman et al 50 demonstrated that paper and computer modeling of open thoracotomy did not increase procedural accuracy.…”
Section: Current Literature On Simulation‐based Procedural Traininmentioning
confidence: 99%
“…Agreement with the checklist and performance standard among an expert panel of physicians, consistent performance scores between 1‐week pretraining tests and same‐day pretraining tests, and improvement in posttraining performance measures all provide construct validity 19 to the assessment methodology. Concurrent validity (correlation with other assessment measures for the procedure) 20 and discriminant validity (ability to produce results that are different from another validated test) 21 were not measured because no other published assessment methods for this procedure are available for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Some have used animal cadavers and rib cages, live dogs, mannequins and human cadavers; some of these are expensive and not practical in every skills lab. [12][13][14][15] Interestingly, very few have been rigorously tested for their validity in training as well as assessment. This article describes a model which is practical and affordable, using porcine ribs mounted on a resin cast of a human thorax.…”
Section: Introductionmentioning
confidence: 99%